The Effect of Adding Fibers on Dry Shrinkage of Geopolymer Concrete - Frayyeh, Qais J.; Kamil, Mushtaq H. (Salehan Institute of Higher Education, 2021)
Despite their drastically different chemical ingredients and interactions, geopolymer concrete exhibits many of the same features as ordinary concrete. Among these properties is drying shrinkage. As in normal concrete, dry shrinkage in geopolymer concrete may cause cracking if the geopolymer concrete is bound, which affects the integrity of the structure in the future. It's important to measure drying shrinkage as soon as possible because it's the cause of early age cracking, which happens when the concrete isn't very strong. The purpose of this study is to determine how to reduce the dry shrinkage value of geopolymer concrete by using different types of fibers. Three types of fibers were used to determine their effect on the dry shrinkage of geopolymer concrete when compared with a reference mixture without the fibers. Metakaolin was used as a binder for the concrete geopolymer. As for the fibers, steel, carbon and polypropylene fibers were used in proportions of (0, 0.5, and 1%). The results showed an improvement in dryness shrinkage when adding fibers in general, with a difference in values between the different types of fibers. Steel fibers had the lowest amount of dry shrinkage. The temperature had a direct influence on the decrease in the extent of the shrinking, since the samples handled at higher temperatures had less dryness to begin with.Â Doi: 10.28991/cej-2021-03091780 Full Text: PDF